2022
DOI: 10.3390/ijerph191912764
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Health in Urban Areas with a Mediterranean Climate: A Conceptual Framework with a Social and Climate Justice Approach

Abstract: The consequences of climate change are becoming increasingly evident and highlight the important interdependence between the well-being of people and ecosystems. Although climate change is a global phenomenon, its causes and consequences vary dramatically across territories and population groups. Among settings particularly susceptible to health impacts from climate change are cities with a Mediterranean climate. Here, impacts will put additional pressure on already-stressed ecosystems and vulnerable economies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…The analysis of extreme weather events in Annaba city revealed a noticeable warming trend in Annaba city, with prolonged extreme climate conditions observed particularly during July, as well as significant shifts in temperature dynamics and increased urban temperatures attributed to the urban heat island effect. This warming trend is consistent with global climate change patterns observed worldwide, aligning with different climates [12,15,60,61]. The increase in temperatures over the recent four-year span from 2020 to 2023, and the projected warming trend from 2024 to 2029, globally suggest a significant shift in climate dynamics in the Mediterranean region, which is already found in previous studies [62,63].…”
Section: Extreme Weather Eventssupporting
confidence: 90%
“…The analysis of extreme weather events in Annaba city revealed a noticeable warming trend in Annaba city, with prolonged extreme climate conditions observed particularly during July, as well as significant shifts in temperature dynamics and increased urban temperatures attributed to the urban heat island effect. This warming trend is consistent with global climate change patterns observed worldwide, aligning with different climates [12,15,60,61]. The increase in temperatures over the recent four-year span from 2020 to 2023, and the projected warming trend from 2024 to 2029, globally suggest a significant shift in climate dynamics in the Mediterranean region, which is already found in previous studies [62,63].…”
Section: Extreme Weather Eventssupporting
confidence: 90%
“…Several studies on health systems resilience to climate change are proposed in the scienti c literature [6,8,[19][20][21][22][23][24][25]. The results presented in this article take into account these studies but present important singularities.…”
Section: Discussionmentioning
confidence: 99%
“…Drought is considered a psychological stressor (Yusa et al 2015 ; US climate resilience toolkit 2019 ) and even just the threat of climate change and its expected consequences, including drought, are important psychological and emotional stressors (Marí-Dell'Olmo et al 2022 ; Dodgen et al 2016 ), especially for the younger population, that report, among others, feelings of sadness and anxiousness that affect their daily life (Hickman et al 2021 ). Moreover, important hormonal and metabolic pathways related to chronic psychological stress can affect human health (Epel 2009 ).…”
Section: Drought Impact On Mental Healthmentioning
confidence: 99%
“…The detrimental impact of droughts on human health, other than mental health, has been evidenced by several studies that have found significant associations with cardiovascular problems (Berman et al 2017 ), respiratory problems (Yusa et al 2015 ), cancer (Stanke et al 2013 ) increased risk of certain infectious diseases (Yusa et al 2015 ; Stanke et al 2013 ; Salvador et al 2020a ) and mortality from different causes (Berman et al 2017 ; Salvador et al 2020a ; Salvador et al 2020b ; Salvador et al 2020c ; Salvador et al 2021 ). Moreover, extreme temperatures, that are related to droughts, have additionally been associated to worsening of cerebral and gastrointestinal diseases, to diabetes and to renal disorders (Marí-Dell'Olmo et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%